Integration of Frequency Dependent Soil Electrical Properties in Grounding Electrode Circuit Model - Mehrdad Mokhtari; Zulkurnain Abdul-Malek; Chin Leong Wooi (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The effect of frequency dependent soil properties on the impedance and transient response of the grounding electrode was investigated. The frequency dependent soil models as proposed by Scott, Smith-Longmire, and Visacro-Alipio were critically reviewed. A novel method was proposed to integrate the frequency dependent soil electrical properties in the circuit model of grounding electrode. To validate the application of the method in circuit model, the voltage responses of the grounding electrode obtained by the circuit and electromagnetic models were compared. The voltage responses obtained by the circuit and electromagnetic models were in excellent agreement in terms of voltage peaks and wave shapes. The differences between voltage peaks obtained by the circuit and electromagnetic models were found less than 1%.